Development and Application of an Indirect Enzyme‐Linked Immunosorbent Assay Based on a Recombinant Matrix Protein for the Serological Study of Porcine Deltacoronavirus in Mexican Pigs - Francisco Jesus Castañeda Montes; José Luis Cerriteño Sánchez; Julieta Sandra Cuevas‐Romero; María Azucena Castañeda Montes; Susana Mendoza Elvira (Veterinary Medicine and Science)
ABSTRACT Porcine deltacoronavirus (PDCoV) is an infectious disease that causes diarrhoea in pigs of different ages; however, piglets are more susceptible. PDCoV was first reported in 2012 in China and Hong Kong. Later, it was first reported in the USA in 2014 and in Mexico in 2019. Several studies have shown that M protein is highly conserved and, therefore, suitable for diagnostic systems. In this study, for the first time, an indirect enzyme‐linked immunosorbent assay (iELISA) based on a recombinant M protein (rM‐PDCoV) was developed to evaluate the seroprevalence of PDCoV in four states in Mexico. High sensitivity (83%) and specificity (100%) were observed for the iELISA. The kappa index calculated a nearly perfect agreement (0.8831) compared to the Western blot (gold standard test), suggesting acceptable statistical value support. In this study, 50.38% of the serum samples from backyard pigs were PDCoV‐positive. The serological comparison showed that PDCoV/PEDV coinfections occurred in 31.98% of the analysed sera. These results can enrich our understanding of how this virus spreads and enable the evaluation of PDCoV infections. Moreover, it highlights the importance of continually investigating the seroprevalence of PDCoV in Mexico because there is also no information about the current prevalence of the disease.